Learning English through local wisdom-based Toba boat race edu game - Ika Agustina; Gunawan; Andrian; Reniwati Lubis; Rommel Sinaga (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
Educational games represent a transformative innovation in contemporary learning, integrating pedagogical objectives with engaging, game-based experiences that capture students’ interest. This study seeks to design an Android-based English educational game that embeds the local wisdom and cultural heritage of the Lake Toba community. Employing a Research and Development approach, the study first collected English vocabulary and terminological phrases from dictionaries, encyclopedias, and relevant references. The second stage involved gathering words and expressions rooted in the unique cultural characteristics and local traditions of the Lake Toba area. Students’ responses to the Toba Boat Race game indicate a highly positive reception. Beyond enhancing students’ English vocabulary, the Toba Boat Race game fosters deeper appreciation and understanding of local wisdom, making it a culturally responsive innovation ready for broader distribution among junior high school learners.